Response of granite residual soil slopes under dry–wet cycles - Mao, Qiang; Guo, Kai; Zhang, Jiangwei; Xiao, Guangning; Du, Jianhang; Cheng, Xiaohui; Guo, Hongxian (Frontiers in Earth Science, 2024)
Granite residual soil is widely distributed in the southern coastal areas of China, and the slope of granite residual soil is prone to instability and failure under the alternating action of rainfall and drying, which will cause great disasters to human society. In order to study the response mechanism of granite residual soil slope under the alternating action of rainfall-drying-staticrainfall, this study study on the dry and wet cycle response of granite residual soil slope through the method of indoor scaling model test, presented the response process of the slope under the action of dry and wet cycle, and discussed the change law of slope deformation, water content and matrix suction. The results show that: under the alternating action of rainfall-drying-static-rainfall,(1) the network cracks on the slope form a dominant channel of rainwater seepage, which is the main reason for the rapid decline of soil anti-sliding ability in a short time; (2) Under the rainfall intensity of 1.7-2.4mm/min, the erosion effect of rain on the slope is obviously stronger than that of osmotic erosion, and the surface erosion failure of the granite residual soil slope tends to occur without obvious sliding surface; (3) After the loss of matric suction for a period of time, the phenomenon of channelling and loss failure on the slope is a sufficient condition for slope instability failure, but not a necessary condition. The above research results are expected to provide the basis and reference for preventing and controlling the landslide hazard of granite residual soil slope under similar conditions.